Efektivitas Pelatihan Self Management Berbasis Goal Setting terhadap Personal Growth Initiative pada Peer Counsellor UIN Malang - Hanum Amanda Mahfud; Salsabila Diandra; Muhammad Jamaluddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Personal Growth Initiative (PGI) refers to an individual's ability to actively and intentionally engage in the process of personal development. This ability is essential for peer counsellors because they serve as psychological support providers and positive role models for their peers. This study aimed to examine the effectiveness of goal setting-based self-management training in improving Personal Growth Initiative among peer counsellors at UIN Malang. This study employed a quantitative experimental approach using a one group pre-test post-test design. The participants consisted of 10 active peer counsellors aged 19–20 years who were selected using a purposive sampling technique. Data were collected using the Personal Growth Initiative scale adapted from the Personal Growth Initiative Scale-II (PGIS-II). The intervention was conducted through two training sessions consisting of assessment, cognitive reconstruction, and behavioural modification through goal setting, self-monitoring, and self-evaluation. The results showed an increase in the average PGI score from 69.90 to 79.30 after the intervention. The Wilcoxon Signed-Rank Test analysis indicated a significant difference between pre-test and post-test scores (Z = −2.701; p = 0.004 < 0.05). These findings indicate that the training improved participants' ability to establish goals, manage themselves, and perform intentional actions toward personal development. In conclusion, goal setting-based self-management training is effective in improving Personal Growth Initiative among peer counsellors at UIN Malang.